Penatalaksanaan Program “TANGGUH” Pada Kelompok LLT (Layanan Lansia Terintegrasi) Dengan Kearifan Lokal Bali - Yusniawati, Yustina Ni Putu; Putra, I Gde Agus Shuarsedana; Dari, Ni Putu Desy Ratna Wulan; Lewar, Emanuel Ileatan; Maharyawan, I Wayan Agus; Devi, Ni Putu Lusiana; Dewi, Ni Nyoman Ari Kundari; Parwati, Putu Atika (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2026)
Background: The elderly are a vulnerable group requiring special attention, particularly regarding degenerative diseases like hypertension. In Melinggih Village, there are around 250 elderly residents, but participation in village activities is very low (only 57 are active). The main issues include limited information on degenerative diseases, a lack of skills in preparing traditional medicine, and weak cadre capacity in designing productive activities. Based on these conditions, this community service program (PKM) was implemented to improve the quality of life, health, independence, and productivity of the elderly, supporting the Indonesia Emas 2045 Vision and SDGs targets. Method: The research team partnered with the elderly group. Implemented solutions included education on degenerative diseases, training in making celery-based herbal drinks using Balinese local wisdom to lower hypertension, cadre mentoring, and elderly gymnastics. The program concluded with a comprehensive evaluation of participants' knowledge and skills. Results: Active activities were structured to increase elderly productivity: 1) Elderly gymnastics, educational activities, and active mentoring were conducted with the PKM team, cadres, and elderly in Melinggih Village regarding hypertension, resulting in increased knowledge and skills in managing elderly hypertension. 2) The elderly learned to make herbal drinks from celery. 3) Health cadres appeared active and collaborated well with the PKM team. Conclusion: Education on degenerative diseases, specifically hypertension, went well, successfully increasing cadres' and the elderly's understanding of their conditions to optimize health awareness. Training on traditional medicine preparation, specifically making celery drinks to lower hypertension, also progressed successfully.